Secondary injury prevention program may decrease contralateral ACL injuries in female athletes: 2-year injury rates in the ACL-SPORTS randomized control trial - Johnson, Jessica L. (J Orthop Sports Phys Ther, 2020)
OBJECTIVE: To determine if the addition of perturbation training to a secondary injury prevention program reduced the rate of second anterior cruciate ligament (ACL) injuries compared to the prevention program alone. DESIGN: single-blinded randomized control trial METHODS: Thirty-nine female athletes who intended to return to cutting/pivoting sports were enrolled 3-9 months after primary ACLR. Athletes were randomized into either progressive strengthening, agility, plyometric, and prevention (SAPP) or SAPP plus perturbation training (SAPP+PERT) groups; each had ten sessions over 5 weeks. Occurrence and side of second ACL injury were recorded for two years after primary ACLR. RESULTS: There were nine second ACL injuries in the two years after ACLR. There was no statistically significant difference in rate or side of second ACL injury between the SAPP+PERT and SAPP groups. CONCLUSION: Adding perturbation training to a secondary ACL injury prevention program did not affect the rate of second ACL injuries in female athletes